2014
DOI: 10.1002/yea.3032
|View full text |Cite
|
Sign up to set email alerts
|

Effects of deletion of different PP2C protein phosphatase genes on stress responses inSaccharomyces cerevisiae

Abstract: A key mechanism of signal transduction in eukaryotes is reversible protein phosphorylation, mediated through protein kinases and protein phosphatases (PPases). Modulation of signal transduction by this means regulates many biological processes. Saccharomyces cerevisiae has 40 PPases, including seven protein phosphatase 2C (PP2C PPase) genes (PTC1-PTC7). However, their precise functions remain poorly understood. To elucidate their cellular functions and to identify those that are redundant, we constructed 127 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 47 publications
(56 reference statements)
0
17
0
1
Order By: Relevance
“…Another interesting feature is the downregulation of Ptc2 in the CEN.PK strain compared to ADY5, a phosphatase protein known to negatively regulate the high-osmolarity glycerol (HOG) pathway, along with Ptc1 and Ptc3 66 . The HOG pathway is a preserved MAPK cascade in S. cerevisiae, which among other functions, is critical for tolerance to different stresses, such as osmotic, citric acid stress and heat stress 67 . Additionally, Panadero et al (2005) showed that the HOG pathway is clearly activated in response to a downshift in temperature from 30 °C to 12 °C, participating in the transmission of the cold signal and on the regulation of the expression of a subset of cold-induced genes 68 .…”
Section: Response Of Cenpk Strain Versus Ady5 Strainmentioning
confidence: 99%
See 1 more Smart Citation
“…Another interesting feature is the downregulation of Ptc2 in the CEN.PK strain compared to ADY5, a phosphatase protein known to negatively regulate the high-osmolarity glycerol (HOG) pathway, along with Ptc1 and Ptc3 66 . The HOG pathway is a preserved MAPK cascade in S. cerevisiae, which among other functions, is critical for tolerance to different stresses, such as osmotic, citric acid stress and heat stress 67 . Additionally, Panadero et al (2005) showed that the HOG pathway is clearly activated in response to a downshift in temperature from 30 °C to 12 °C, participating in the transmission of the cold signal and on the regulation of the expression of a subset of cold-induced genes 68 .…”
Section: Response Of Cenpk Strain Versus Ady5 Strainmentioning
confidence: 99%
“…Additionally, Panadero et al (2005) showed that the HOG pathway is clearly activated in response to a downshift in temperature from 30 °C to 12 °C, participating in the transmission of the cold signal and on the regulation of the expression of a subset of cold-induced genes 70 . So, the downregulation of Ptc2, which directly dephosphorylates Hog1 MAPK and limits the maximal activation of the HOG pathway 69 , may be related to this need to activate this pathway.…”
Section: Response Of Cenpk Strain Versus Ady5 Strainmentioning
confidence: 99%
“…Phosphorylation of Slt2 occurs at Tyr and Thr residues in a T-X-Y motif within the activation loop common to MAPKs [see Levin (2011) for a review]. In keeping with the involvement of Ptc1 in the CWI pathway, ptc1 mutants are sensitive to diverse cell-wall antagonists such as calcofluor white (CFW), Congo red, caffeine, and caspofungin (Ram et al 1994;Markovich et al 2004;Sharmin et al 2014) or to other conditions that activate the CWI pathway, such as alkaline pH . In addition, the ptc1 mutation is synthetically lethal with mutations in genes that are important for cell-wall construction, such as FKS1, GAS1, and SMI1 ( Lesage et al 2004).…”
mentioning
confidence: 99%
“…It is remarkable that, though the type 2C phosphatase family is composed of six additional members (Ptc2 to Ptc7) we never recovered a PTC gene as ptc1 suppressor. This reinforces the notion that most biological properties of Ptc1 are not shared by other members of the gene family (Gonzalez et al ., ; Gonzalez et al ., ; Sharmin et al ., ). Although several of the suppressor genes were able to alleviate many ptc1 related phenotypes (i.e.…”
Section: Discussionmentioning
confidence: 97%